Edukasi Pemilahan Sampah dalam Meningkatkan Pengetahuan, Sikap, dan Tindakan Siswa Sekolah Dasar Kota Palembang - Meiranda Dwinissa Kesuma; Intan Kumalasari; Hendawati Hendawati (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The issue of solid waste is becoming increasingly complex in line with population growth and the expansion of residential areas, while the capacity of final disposal sites remains very limited. The absence of waste segregation at the source leads to accumulation, contributing to environmental pollution, the spread of diseases, and flooding due to clogged drainage channels. This study aimed to analyze changes in students’ knowledge, attitudes, and practices before and after a waste-sorting educational intervention at SD Negeri 119 Palembang in 2025. A pre-experimental design with a one-group pretest–posttest approach was employed, involving 104 fifth-grade students selected through total sampling. The intervention consisted of waste-sorting education using audio-visual media, accompanied by pretest and posttest assessments. The findings revealed significant improvements in students’ knowledge (67.40 to 91.15), attitudes (23.28 to 32.56), and practices (12.72 to 22.90). The Wilcoxon test confirmed statistically significant differences between pre- and post-intervention scores (p < 0.05). These results highlight that audio-visual media–based education is effective in enhancing students’ knowledge, attitudes, and practices regarding waste sorting. Continuous implementation of similar programs in schools is strongly recommended to foster environmentally responsible behavior from an early age.